Antimicrobial potential of bioactive resin composites in caries management: a systematic review of in vitro studies - Lopes, Sara; Lopes, Pedro C.; Fidalgo-Pereira, Rita; Flores-Fraile, Javier; Veiga, Nélio; Gomes, Ana T. P. C. (Frontiers in Oral Health, 2025)
IntroductionSecondary caries is the leading cause of failure in resin composite restorations due to biofilm accumulation. Bioactive resin composites (BRCs) release ions that promote remineralization and inhibit bacterial growth. This review compares microbial adhesion and antimicrobial effectiveness between BRCs and conventional resin composites.MethodsA systematic search was conducted in databases PubMed, Scopus, and Cochrane Library to identify in vitro studies evaluating bacterial adhesion and antimicrobial effect of commercially available bioactive resin composites and their comparison with conventional resin composites. Studies reporting on microbial adhesion and/or antimicrobial effects were included.ResultsA total of 272 potentially relevant articles were identified. Following PRISMA guidelines, eight articles met the inclusion criteria. The studies focused on five commercially available BRCs: Activa Bioactive Restorative (ACT), Beautifil II (BE), Cention N (CN), Equia Forte (EF), and SDR Flow Plus. Most studies assessed the adhesion of Streptococcus mutans in isolation. While microbial adhesion was observed on both bioactive and conventional resin composites, cell viability differed, with BRCs demonstrating superior antimicrobial effects.ConclusionBacterial adhesion to dental restorative materials is influenced by surface roughness, hydrophilicity, chemical composition, and ion release. This review suggests that BRCs and conventional resin composites exhibit similar surface characteristics, resulting in comparable bacterial adhesion. However, BRCs show greater efficacy in reducing bacterial viability, probably due to ion release, which modulates the local microenvironment and microbial dynamics. Further research is needed to explore the broader impact of ion release on the oral microbiome and its potential role in dysbiosis and disease progression.Systematic Review RegistrationOSF Registries, https://doi.org/10.17605/OSF.IO/HRKFV